Newly Discovered Topological Insulator Sr3SnO for Spintronics, Optical and Electronic Properties - Amrane, N.; Adnan Moh’d, Rasha W.; Lucman, Juwayni; Safieh, Faris Mahmoud; Benkraouda, Maamar (JOURNAL OF ADVANCES IN PHYSICS, 2018)
A theoretical study of the electronic and optical properties of dilute magnetic semiconductor Sr3SnO is presented, using the full potential linearized augmented plane wave method. The Perdew Burke Ernzerhof (GGA08) (generalized gradient approximation) is used for the total energy calculations, while the Modified Becke Johnson (MBJ) is used for electronic structure calculations since this functional was designed to reproduce as well as possible the exact exchange correlation potential rather than the total energy, and as a result gives significantly improved results such as band gap and electronic structure. In this study, we have investigated the optical properties by means of first-principles density-functional total-energy calculation using the all-electron full potential linear augmented plane-wave method (FPLAPW).